(untitled) (Entrepreneurship Journal for Finance and Business, 2022)
This research adopts a model that is reflected in its main objective on studying the concept of ethical leadership and its role in improving the performance of teaching staff in relation to ethical leadership behaviors and proving its relationship to teacher commitment. To achieve this, the research scale was built based on the dimensions of ethical leadership and performance by constructing a questionnaire (research tool), which consists of 20 questions divided equally on each dimension, which was aimed first at the perception of ethical leadership and the factors that affect ethical leadership as well, as well as improving performance among The research sample. The research presents the fundamental importance in exploring the perception of the teaching staff in the judiciary of knowledge of ethical leadership practices and their role in improving their performance and to what extent the dimensions of ethical leadership or behaviors and influence on their ethical leadership practice are related. In order to reach the objectives of the study, by relying on the analytical descriptive approach, the data was collected in a comprehensive inventory method, as it was applied to the teaching staff in a number of schools in the district of science in Salah al-Din governorate, which represents the research community. The number of distributed questionnaires reached (140) questionnaires, (112) of them, or 80%, which represents the approved sample of the study valid for statistical analysis, and it was analyzed according to the statistical analysis program SPSS.V22, based on the statistical indicators (arithmetic mean, standard deviation, percentage of difference factor and T-test). The study came out with several conclusions, the most important of which is that: (a) ethical leadership positively affects the performance of teaching staff, (b) school leadership plays a positive role in promoting ethical behaviors among its educational cadres, and the study made several recommendations, including: Strengthening the moral qualities represented by justice, cooperation, firmness and trust Self-leadership of the surveyed schools as it governs their relationship with others and improves the level of individual and overall performance in the organization.